(untitled) (Revista Lusófona de Economia e Gestão das Organizações, 2018)
The economic growth of a country depends on many factors. One of them is innovation, which focuses primarily on the creation and development of new ideas and subsequently in its practical application. It should be analysed from a technological development point of view and so the number of researchers, the research investment and the type of research (basic and applied) are essential to this analysis. In order to perform this analysis and determine the importance of innovation for economicgrowth in Portugal in the period 2000 - 2013, were made two models of multiple linear regression. It was concluded that the higher the percentage of researchers in companies or the synergies between researchers in companies and universities, then economic growth will be favoured. Similarly, technological innovation is a reflection of research by scientists and engineers and thus contribute more strongly that research done in other areas, such as social sciences.